The Development of Enrichment Curriculum to Enhance Future Work Skills for Secondary Students in the Opportunity Expansion School of Office of the Basic Education Commission - Namjai, Nawaphat; Kamtubtim, Varaporn; Srisuantang, Sunti (The Journal of Development Administration Research, 2025)
This study aims to 1) assess the needs for future work skills among lower secondary school students in educational opportunity expansion schools under the Office of the Basic Education Commission (OBEC) 2) develop a supplementary curriculum to enhance future work skills for these students and 3) examine the effectiveness of the supplementary curriculum. This research follows a Research and Development (R&D) design. The study was conducted at Wat Chotikaram School, under the Nonthaburi Primary Educational Service Area Office 1. The sample consisted of 30 lower secondary school students from Wat Chotikaram School, selected through purposive sampling. The research instruments included 1) in-depth interviews 2) questionnaires 3) a future work skills assessment form, and 4) a satisfaction evaluation form. Data were analyzed using percentage, mean, standard deviation, and the Priority Needs Index (PNI) modified. The results showed that: 1) The five most critical future work skills identified by employers and stakeholders were social intelligence, creativity and adaptability, advanced data analysis, computational thinking, and collaboration in virtual environments 2) The supplementary curriculum, designed to address these skills, included principles, objectives, content structure, learning activity processes, and evaluation methods. Expert reviews rated the curriculum as highly appropriate 3) The study on the effectiveness of the supplementary curriculum, involving 30 participating students, revealed a statistically significant improvement in future work skills. Post-learning average scores demonstrated a notable enhancement in skill development. Furthermore, students assessed the activities as highly beneficial and well-aligned with their needs. These findings highlight the suitability of the curriculum content and the effectiveness of the learning activity processes following its implementation.